(untitled) (Research, Society and Development, 2025)
Reflecting on this topic, it is clear that different management approaches are the result of the people who implement them, and the results of these practices depend profoundly on each individual’s understanding of the world and the realities of others. Thus, the objective of this study is to analyze school management and the democratization of education through a literature review. Its specific objectives are: to highlight what school management is; to demonstrate school management and democratic teaching strategies; and to examine the defining approaches of educational management, as well as strategic management. The methodology used is qualitative bibliographic research. It was found that the concept of school management has evolved, taking responsibility for promoting human development within its environment. School management, like other areas of activity, today requires competencies aligned with the challenges of Brazilian society, moving beyond a managerial and administrative focus and emphasizing skills in human relations, leadership engaged in the pursuit of better learning, and the use of innovative technologies.